Discrimination against undergraduate students of Medicine in the research field. - Lobo-Salas, Yulis Fernanda (2022)
The objective of this article is to publicize the value of the investigation for physicians in training, as well as reviewing the factors influencing the lack of opportunities for difusión and publication of the generated products from it taking into account that the access to research opportunities is limited and the publication rates is low. Articles were searched in Google Scholar and PubMed whose main topic was research in undergraduate medicine having as subthemes the publications and its inclusión in the formative process. In the process was found that undergraduate investigation is vitally important for the training of integral physicians and for the acquisition of skills of great utility in medical practice such as responsibility and critical thinking so it is necessary to encourage its development in higher education.